Correctional mental health handbook - Ax, Robert Kirk, 1952-; Fagan, Thomas J., 1949- (Sage Publications, 2003)
The Correctional Mental Health Handbook is the first book to offer a comprehensive overview of the services provided by correctional mental health professionals for the various populations found in correctional programs and facilities. Edited by Thomas J. Fagan and Robert K. Ax, experts with over 40 years of correctional mental health experience, this unique handbook is divided into three sections. The first section provides a flexible model for organizing mental health services based on staffing levels, facility mission, and local need. The second section considers typical offender problems.